Laboratory Fabrication of Gold Occlusal Surfaces for Removable and Implant-Supported Prostheses - Patrick M. Lloyd, DDS, MS (Journal of Prosthodontics, 2003)
This article describes a technique for fabricating prosthetic teeth with gold occlusal surfaces for removable or implant-supported prostheses